THE FORMULATION OF “ZILLICUM TEA” FROM GINGER (Zingiber officinale var. amarum), STAR ANISE (Illicium verum), AND LEMONGRASS (Cymbopogon citratus) TOWARD ANTIOXIDANT ACTIVITIES AND HEDONIC ACCEPTABILITY - Manao, Nancy Felicia; Handoko, Yoga Aji (AGROLAND The Agricultural Sciences Journal (e-Journal), 2025)
Zillicum tea is an innovations herbal tea product formulated from combination of three plants: ginger, lemongrass, and star anise. These three plants were selected for their functional value, particularly their antioxidant compounds. The purpose of this research was to determine the effect of antioxidant activity and hedonic acceptability properties of the three combinations of Zillicum tea formulation, and to identify the best of formulation based on these parameters. This research used a Completely Randomized Design (CRD) with four treatments(the combination of ginger, star anise, and lemongrass), specifically F1, F2, F3, F4 with five replications. Antioxidant activity and organoleptic properties are the primary parameters, while moisture content and total plate count test are supporting parameters. The result F4 formulations exhibited antioxidant activity of 54.41% inhibition (p < 0.05), which was significantly higher than that of F1 (33.20%), F2 (39.86%), and F3 (43.00%). Furthermore, the organoleptic taste score of F4 (5.28 ± 1.27) was also significantly greater comparased to the other formulations.